Watermelon stomach seen by wireless‐capsule endoscopy - MASCARENHAS‐SARAIVA, M. (2003)
Endoscopy. 2003 Jan;35(1):100. Watermelon stomach seen by wireless-capsule endoscopy. Mascarenhas-Saraiva M, Lopes L, Mascarenhas-Saraiva A. SourceDigestive Endoscopy and Motility Unit, Trindade Hospital, Rua Trinidade 115, 4000-541 Porto, Portugal. miguelms@manoph.pt PMID:12510242[PubMed - indexed for MEDLINE]